2013
DOI: 10.1111/jawr.12121
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Hydrologic and Water Quality Benefits of a Network of Stormwater Control Measures in a SE U.S. Piedmont Watershed

Abstract: The hydrologic and water quality benefits of an existing engineered stormwater control measures (SCMs) network, along with the alternative stormwater control simulations, were assessed in the rapidly urbanizing Beaverdam Creek watershed located in SE U.S. Piedmont region through the use of distributed Model of Urban Stormwater Improvement Conceptualization stormwater model. When compared with predevelopment conditions, the postdevelopment watershed simulation without SCMs indicated a 2 times increase in total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Model simulation results suggest reductions in peak flows and surface runoff, and increases in evapotranspiration and subsurface flow and infiltration, with all spatial configurations of LID at the watershed scale. This is consistent with Gagrani et al [19], Fry and Maxwell [53], and Avellaneda et al [54], who reported similar effects on water balance components and peak flows after the placement of different LID practices in urban watersheds, with 42-55 percent impervious surfaces and drainage areas ranging from 0.2 km 2 to 12 km 2 .…”
Section: Lid Practices and Watershed-scale Hydrological Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…Model simulation results suggest reductions in peak flows and surface runoff, and increases in evapotranspiration and subsurface flow and infiltration, with all spatial configurations of LID at the watershed scale. This is consistent with Gagrani et al [19], Fry and Maxwell [53], and Avellaneda et al [54], who reported similar effects on water balance components and peak flows after the placement of different LID practices in urban watersheds, with 42-55 percent impervious surfaces and drainage areas ranging from 0.2 km 2 to 12 km 2 .…”
Section: Lid Practices and Watershed-scale Hydrological Effectssupporting
confidence: 88%
“…The results from the subwatershed with smaller LID lots and underdrain connections showed a substantial reduction in peak discharge (up to 33%) and total storm runoff (up to 40%). Additionally, recent field-based research provides evidence of the cumulative watershed scale effects of LID on hydrologic responses, such as peak flows and pollutant loads [17][18][19][20]. Such experimental studies can be resource intensive (e.g., financial, personnel, time) [21]; however, process-based models provide a means to go beyond measured data and explore the projected "what if" LID scenarios using potentially less resources.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of connectivity to SCMs on runoff ratios were more dramatic in warmer months (May to September) than the rest of the year (Figure a), which supports the assertion that evaporation is the physical process behind these relationships. Other studies have demonstrated the existence of such a relationship between SCM connectivity and runoff volumes, but these relationships are often stronger (Gagrani et al, ; Hale et al, ; Liu et al, ). While monotonic, the relationship appears to be nonlinear, shown in Figure a by the hockey‐stick shape and in Figure a by the increasing distance between vertically stacked points as UI/TI increases, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The Beaverdam Creek watershed is an urbanizing watershed near Charlotte, North Carolina, where streamflow and water quality was monitored for 9 years (Figure a; Allan et al, , ; Allan & Diemer, ). The most urbanized subwatershed of the greater Beaverdam Creek watershed, called BD4, is the subject of this study and has been the subject of other recent studies of hydrology and water quality (Bell, McMillan, et al, ; Gagrani et al, ; Jefferson et al, ). BD4 is 1.8 km 2 in area and is built out with a medium‐density residential neighborhood in the lower elevations of the watershed and an interstate exchange and commercial shopping center in the upper watershed (Figure b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation